Effects of vinasse on sugarcane (Saccharum officinarum) productivity - Gómez, J.; Rodríguez, O. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2011)
Vinasse is a corrosive and contaminant industrial liquid residue from alcohol distillation. Vinasse contains high levels of organic matter, potassium, calcium and moderate amounts of nitrogen and phosphorus. The effects of several applications of mineral fertilization combined with vinasse on sugarcane productivity were evaluated, on plant-cane, first and second ratoon seasons (92-95). The experiment was established using a randomized split plot design with four replications. Treatments consisted of 3 chemical fertilizer doses in the main plots as: F0= 0 kg ha-1; F1= 180 kg ha-1 N + 160 kg.ha-1 P2O5 + 220 kg ha-1 K2O; F3= 80 kg ha-1 N + 45 kg.ha-1 P2O5 combined with 5 vinasse doses in the subplots as V0=0 m3.ha-1, V1=25 m3.ha-1, V2=50 m3.ha-1, V3=75 m3.ha-1 and V4=100 m3 ha-1. Sugar and cane yields increased with application of vinasse. Best results were obtained when using vinasse as 50 m3 ha-1 on plant-cane and 100 m3 ha-1 on first and second ratoons. The N, P2O5 and K2O sugarcane demands were supplied by the 50 m3 ha-1 vinasse dose (V2) in proportions of 55%, 72% and 100% respectively. Vinasse application demonstrated its efficiency as fertilizer material as well as reducing vinasse contaminant effects to waterways.